The existence of Dark energy leaves no room for Darkmatter - Harutyunian, H. A.
Dark matter was introduced into science to reconcile observational data with the dominant cosmogonic ideas. According to these ideas, all baryon configurations in our Universe are believed to be dynamically balanced, to which the virial theorem is applicable. However, the discovery of dark energy changed the situation drastically. Self-consistent application of physical laws to the process of interaction between baryon matter and the carrier of dark energy allows one to conclude that all baryon configurations are constantly gaining energy and cannot be balanced. Therefore, the need to introduce dark matter disappears, and the only inevitable conclusion is the rejection of dark matter, since it does not exist.
Keywords: Astronomy